IMPLEMENTASI KEBIJAKAN BANTUAN SOSIAL BIAYA PENDIDIKAN MELALUI PROGRAM KARTU JAKARTA PINTAR (KJP) PLUS DI SMAN 83 KECAMATAN CILINCING KOTA JAKARTA UTARA - Abdurrazak, Riza; Hayu Dwimawanti, Ida; Djumiarti, Titik (Jurusan Administrasi Publik, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Diponegoro, 2024)
The Jakarta Smart Card (KJP) Plus program is a DKI Jakarta Provincial Government program in the education sector as an effort to improve the quality of education in DKI Jakarta which is guided by Governor Regulation Number 110 of 2021 concerning Social Assistance for Education Fees. SMA Negeri 83, Cilincing District, North Jakarta City is one of the schools with the most KJP Plus users in Cilincing District. But it's still there obstacles in the policy implementation process. This research aims to analyze the implementation process of KJP Plus using the 5 accuracy theory according to Riant Nugroho and identify supporting and inhibiting factors for KJP Plus through the combination theory of Van Meter and Van Horn Edwards III at SMA Negeri 83 Cilincing District, North Jakarta City. This research uses descriptive qualitative methods with purposive sampling techniques. Data sources through interviews and documentation. The results of the research show that the implementation of KJP Plus has been carried out, but has not run optimally in the aspects of policy accuracy, target accuracy and environmental accuracy. Then, there are supporting factors in the implementation of the social assistance policy for education costs at SMAN 83, Cilincing District, North Jakarta City, namely the characteristics of the implementing agent, communication and attitude of the implementer, while the inhibiting factors are the policy standards and targets as well as economic, social and political conditions. The suggestions from this research are increasing understanding from all levels of society and implementers regarding the benefits and objectives of KJP Plus, involving schools and the community in determining targets, increasing the acceleration of disbursement of funds, reintroducing the collection of reports on the use of funds with shopping receipts, and providing special assistance to parents when collect files.